The association between pineal gland calcification and white matter hyperintensities of presumed vascular origin in older adults. A population-based study. (February 2020) - Del Brutto, Oscar H.; Mera, Robertino M.; Castle, Paul; Kiernan, Jaydon; Del Brutto, Victor J.; Recalde, Bettsy Y.; Sedler, Mark J.
Highlights: Pineal gland calcification (PGC) has been associated with low melatonin production. Melatonin deficiency may play a role in the development of cerebral small vessel disease (cSVD). We assessed the association between PGC and white matter hyperintensities (WMHs), a biomarker of cSVD. Moderate-to-severe PGC and WMH were independently associated. This study provides grounds for assessing of the role of melatonin deficiency in cSVD development. Abstract: Pineal gland calcification (PGC) has been associated with low melatonin production, a hormone with anti-oxidant, anti-inflammatory, and neuro-protective effects. Therefore, melatonin deficiency may play a role in the development of cerebral small vessel disease (cSVD), a condition that is partly related to upregulation of oxidative and inflammatory mechanisms leading to endothelial dysfunction, breakdown of the blood-brain barrier, and impaired interstitial fluid drainage. In this study, the association between PGC (a surrogate for melatonin deficiency) and white matter hyperintensities (WMHs) of presumed vascular origin (a biomarker of cSVD) was assessed in Atahualpa cohort individuals aged ≥60 years undergoing head CT and brain MRI. PGC was rated as none-to-mild and moderate-to-severe. WMHs were classified according to the modified Fazekas scale. A logistic regression model was fitted to assess the independent association between moderate-to-severe PGC and WMHs. Inverse probability of exposure weighting was used to estimate the effect of PGC on WMH. Of 373 individuals, 96 (26%) had moderate-to-severe PGC and 86 (23%) had moderate-to-severe WMHs. Moderate-to-severe PGC and WMH were independently associated in a fully-adjusted logistic regression model (OR: 2.21; 95% C.I.: 1.19–4.11; p = 0.012). Inverse probability of exposure weighting showed an estimate for the proportion of moderate-to-severe WMH among those with none-to-mild PGC of 20.5%, and the exposure-effect was 13.2% higher among those with moderate-to-severe PGC (β: 0.132; 95% C.I: 0.036–0.229; p = 0.007). The association found in this study provides grounds for further evaluation of the role of melatonin deficiency in cSVD development.